MULTI-PHASE PERMANENT MAGNET SYNCHRONOUS MOTOR USING DIRECT TORQUE ADAPTIVE FUZZY CONTROLLED (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The performance of the conventional direct torque control (DTC-C) scheme, which is primarily based on switching tables or conventional proportional integral (PI) controllers, yields high ripples in torque and magnetic flux, thereby compromising the overall robustness of the system. This research proposes an adaptive fuzzy logic control (AFLC) for controlling a five-phase permanent magnet synchronous motor (5P-PMSM), incorporating the space vector modulation (SVM) algorithm. This approach aims to overcome the limitations of DTC-C schemes. The proposed AFLC-DTC-SVM method is designed to enhance the robustness, response time, and efficiency of the 5P-PMSM drive. Simulation results using MATLAB/Simulink demonstrate that the proposed method significantly reduces torque ripple by approximately 72% compared to the DTC-C technique and 51.16% compared to the DTC-SVM method. Flux ripple is also reduced by 71.42% and 33.33% compared to the DTC-C technique and the DTC-SVM method, respectively. Furthermore, the proposed technique offers robust performance against variations in machine parameters and load disturbances, thereby confirming its superiority over conventional methods.
Keywords: Adaptive fuzzy logic algorithm; Direct torque control; Ripple; Robustness; Five-phase permanent magnet synchronous motor